The Influence of Financial Literacy and Ease of Use on Transactions Using QRIS in MSMEs in Semarang City - Muhammad Rizki Maulana; Entot Suhartono (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The advancement of digital technology in payment systems has prompted micro, small, and medium-sized enterprises (MSMEs) to embrace financial technology, specifically through the implementation of the QR Code Indonesian Standard (QRIS). However, the adoption of QRIS has been inconsistent, particularly within the culinary sector of West Semarang, possibly due to varying levels of financial literacy and technological ease of use. It is disheartening to note that despite the prevalence of QRIS usage in today's society, many businesses in West Semarang have not fully embraced it. The primary objective of this research is to examine how financial literacy and the user-friendliness of QRIS impact the decision-making process of culinary MSMEs in West Semarang when it comes to adopting QRIS, both individually and collectively. Utilising a quantitative approach, the study employs the snowball sampling technique to gather data from 95 participants, following the guidelines set out in the Isaac and Michael Table. The survey used in this study was a Likert scale questionnaire. Various statistical methods including multiple linear regression, t test, F test, and coefficient of determination were employed for data analysis. Findings revealed that both financial literacy and the user-friendliness of QRIS had a significant impact on the adoption of the digital payment system. This suggests that businesses are more inclined to use QRIS when they have a strong understanding of financial concepts and find QRIS easy to use. The research highlights the significance of educating individuals on financial literacy and enhancing accessibility to intermediary services.